Carrying Capacity Based on Environmental Services for Food Supply in Talaga City - Talha Dangkua; Sofyan Muzakir Djibu; Ahmad Syamsu Rijal S; Irawan Matalapu; Indrawan; Karina Meiyanti Maulana (Postgraduate, University of Mataram, 2026)
Environmental Carrying Capacity (ECC) for food supply is the ability of the environment to support population activities through a comparison between the need and availability of food energy. This research aims to provide initial data related to the spatial distribution of ECC for food supply in Talaga Jaya, Telaga, Telaga Biru and Tilango Sub-Districts as part of the city of Talaga and the general conditions of their status descriptions. The Environmental Service Performance Index (ESPI) of the parameters of Landscape, Natural Vegetation and Land Cover was used as a factor in distributing the availability of food energy. Land class and roads distributed population density and food energy needs. The results of the research were analyzed spatially using a supply-demand approach on a grid scale of 0.1 km x 0.1 km. The results found that the spatial distribution of ECC for food supply was in deficit status of 20.03 km2 (11.11%), balanced at 120.86 km2 (67.02%) and surplus at 39.45 km2 (21.88%). Descriptively, the deficit area cannot be covered by the surplus area if there is an energy flow because the high food energy requirement is 64.7 billion kcal/year, while the availability of food energy is only 51.4 billion kcal/year. Thus, the research area has passed the peak of its population growth and is only able to meet the food energy demand for 79.4% of its population. In this case, the government can promote agricultural commodity intensification and diversification policies to meet domestic food energy needs.